Pelatihan Copy Writing Skill bagi Karang Taruna di Kelurahan Bahagia Kecamatan Babelan Kabupaten Bekasi - Rizkia, Muhamad Fajar; Ayu Puspa Nanda; Edi Puryanto (PT. Mitra Jurnal Indonesia, 2024)
This community service aims to improve the writing competence of the community, especially youth organizations and local youth. Apart from that, the writing skills that will be carried out are not just ordinary writing, but utilizing technology and its application based on current developments through copy writing. This starts from a lack of understanding and utilization of writing activities other than formal activities such as school. In this case, introduction, knowledge and training regarding copy writing skills are carried out which can be utilized in the economic and business fields such as marketing. Currently, the search for information, knowledge, product introductions or advertisements is not just about images, but needs to be accompanied by the use of appropriate words and sentences. Therefore, basic knowledge is needed and how to develop appropriate writing according to the objectives. The implementation is carried out for one day which consists of delivering material, exercises and discussions to achieve the expected competencies. Abstrak Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi menulis yang dimiliki oleh masyarakat, terutama karang taruna dan pemuda setempat. Selain itu, kemampuan menulis yang akan dilakukan bukan sekadar menulis biasa, namun memanfaatkan teknologi dan penerapannya berdasarkan perkembangan saat ini melalui copy writing. Hal ini berawal dari kurangnya pemahaman dan pemanfaatan kegiatan menulis selain dilakukan pada kegiatan formal seperti sekolah. Dalam hal ini dilakukan pengenalan, pengetahuan, dan pelatihan terkait copy writing skill yang dapat dimanfaatkan dalam bidang ekonomi dan bisnis seperti pemasaran. Saat ini pencarian informasi, pengetahuan, pengenalan produk atau iklan bukan hanya sekadar gambar saja, namun perlu disertai dengan penggunaan kata serta kalimat yang tepat. Oleh sebab itu diperlukan pengetahuan mendasar dan bagaimana mengembangkan tulisan yang tepat sesuai dengan tujuan. Untuk pelaksanaan dilaksanakan selama satu hari yang terdiri dari penyampaian materi, latihan, dan diskusi untuk mencapai kompetensi yang diharapkan.